2021
DOI: 10.1111/ijfs.15165
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions of a whey–pea protein co‐precipitate

Abstract: The aim of this study was to investigate the mechanisms behind protein-protein interactions in a coprecipitate of whey protein isolate (WPI) and pea protein isolate (PPI). A co-precipitate and blend, consisting of 80% WPI and 20% PPI, were compared. Covalent disulphide interactions were studied by blocking of free thiols with N-Ethylmaleimide (NEM), while electrostatic interactions were studied in systems with 0.5 M NaCl and hydrophobic interactions with 0.2% SDS. Protein solubility, stability and secondary, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Co was prepared using the isoelectric solubilisation/precipitation (ISP) method. Driven by pH, heterogeneous proteins are dissolved and precipitated in the same dispersion system to promote interactions between heterogeneous proteins, such as the formation of disulphide bonds and changes in protein subunit composition, surface charge, solubility, and surface hydrophobicity, thus effectively improving functional properties [ 16 ]. In our previous study, it was proved that Co has superior emulsification [ 17 ] and gel [ 18 ] properties than BL and a single protein.…”
Section: Introductionmentioning
confidence: 99%
“…Co was prepared using the isoelectric solubilisation/precipitation (ISP) method. Driven by pH, heterogeneous proteins are dissolved and precipitated in the same dispersion system to promote interactions between heterogeneous proteins, such as the formation of disulphide bonds and changes in protein subunit composition, surface charge, solubility, and surface hydrophobicity, thus effectively improving functional properties [ 16 ]. In our previous study, it was proved that Co has superior emulsification [ 17 ] and gel [ 18 ] properties than BL and a single protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, the MHC, legumin α, and legumin β protein bands differed significantly in reducing SDS-PAGE, indicating that Co and BL showed different degrees of crosslinking or degeneration with subunits of CPI. Similar studies have suggested that such differences might be attributed to different electrostatic and hydrophobic interactions and the effects of disulfide bond in proteins during preparation of Co by the ISP method [ 10 ]. Co contains a higher number of MHCs, indicating that its functional properties might have some advantages [ 30 ].…”
Section: Resultsmentioning
confidence: 93%
“…Concerning the preparation of Co, heterologous proteins are processed via isoelectric solubilization/precipitation (ISP) [ 9 ]. Driven by pH, proteins from different sources are simultaneously dissolved and precipitated to promote interaction between heteroproteins; generate additional disulfide bonds; change the subunit composition [ 10 ]; and alter the surface charge, solubility, and surface hydrophobicity of the proteins, thus effectively improving their functional properties [ 11 ]. Studies have found that legume–rapeseed Co has better nutritional and functional properties than single protein [ 12 ], and soy–whey protein Co has high water-holding and gel formation capacity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing high-quality protein for nutrition, they are also ideal for fortifying foods (Hoppe et al 2008). More recently, there has been an interest in developing whey protein and plant protein-based combinations such as those derived from pea protein extraction (Kristensen et al 2021). Oats are also used in baked foods, granola bars, dairy and vegan products.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been an interest in developing whey protein and plant protein‐based combinations such as those derived from pea protein extraction (Kristensen et al . 2021). Oats are also used in baked foods, granola bars, dairy and vegan products.…”
Section: Introductionmentioning
confidence: 99%